2023
DOI: 10.3390/microorganisms11071827
|View full text |Cite
|
Sign up to set email alerts
|

Virulence Factor Genes in Invasive Escherichia coli Are Associated with Clinical Outcomes and Disease Severity in Patients with Sepsis: A Prospective Observational Cohort Study

Abstract: Background: Escherichia coli harbours virulence factors that facilitate the development of bloodstream infections. Studies determining virulence factors in clinical isolates often have limited access to clinical data and lack associations with patient outcome. The goal of this study was to correlate sepsis outcome and virulence factors of clinical E. coli isolates in a large cohort. Methods: Patients presenting at the emergency department whose blood cultures were positive for E. coli were prospectively includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Moreover, the isolated antibiotic-resistant E. coli in surface water could be an important carrier and a rich source of emerging and spreading antimicrobial-resistant determinants to other surrounding counterparts [36] . E. coli strains can be classified into different phylogroups, namely, A, B1, B2, C, D, E, and F. Phylogroups A and B1 are sister groups, while phylogroups B2 and D are known to be more virulent [37] . It should be highlighted that isolates from aquatic habitats have been detected in phylogenetic groups A and B1 more frequently than isolates from phylogenetic groups B2 and D [38] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the isolated antibiotic-resistant E. coli in surface water could be an important carrier and a rich source of emerging and spreading antimicrobial-resistant determinants to other surrounding counterparts [36] . E. coli strains can be classified into different phylogroups, namely, A, B1, B2, C, D, E, and F. Phylogroups A and B1 are sister groups, while phylogroups B2 and D are known to be more virulent [37] . It should be highlighted that isolates from aquatic habitats have been detected in phylogenetic groups A and B1 more frequently than isolates from phylogenetic groups B2 and D [38] .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, phylogroup B2 was the most prevalent, followed by phylogroups A, D, and E, respectively. E. coli strains related to the B2 and D phylogroups carry more virulence-associated genes compared to the other phylogroups and are primarily associated with extraintestinal infections, including urinary tract infections [37] . However, our findings are in contrast with previous studies conducted in Portugal, Malaysia, and Iraq that showed a predominance of isolates belonging to the A and B1 phylogenetic groups [39] [41] .…”
Section: Discussionmentioning
confidence: 99%
“…Cytotoxic necrotizing factor 1 (CNF1) is a 110 kDa AB-type protein toxin produced by certain pathogenic strains of Escherichia coli that activates members of the Rho family of small GTPases (Rho, Rac, and Cdc42) involved in cytoskeletal and mitogenic signaling ( 1 ). CNF1-producing E. coli strains are often associated with uropathogenic infections (UPEC strains) ( 2 4 ), neonatal meningitis (NTEC strains) ( 5 9 ), some diarrheal infections ( 10 12 ), and septicemia ( 13 15 ). More recently, the presence of the cnf1 gene has been found in an expanding multidrug-resistant group of extraintestinal pathogenic E. coli ST131 (ExPEC) strains, where it confers a competitive colonization advantage in the gut ( 16 ).…”
Section: Introductionmentioning
confidence: 99%